Prevalence and mechanisms of injuries in water polo: a systematic review - Croteau, F.; Brown, H.; Pearsal, D.; Robbins, S. M. (BMJ Open Sport & Exercise Medicine, 2021)
Objective To summarise the information available in the literature on the prevalence of injuries in water polo and injury risk factors.